2017
DOI: 10.1590/abd1806-4841.201756411
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital warts in pediatric population

Abstract: The approach to children with anogenital warts in the context of sexual abuse is a challenge in clinical practice. This study aims to review the current knowledge of anogenital warts in children, the forms of transmission, and the association with sexual abuse and to propose a cross-sectional approach involving all medical specialties. A systematic review of the literature was conducted in Portuguese and English from January 2000 to June 2016 using the ISI Web of Knowledge and PubMed databases. Children aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 33 publications
1
68
0
3
Order By: Relevance
“…The physicians should suspect for sexual abuse when they encountered with anogenital warts in children. 10,17 Anogenital warts in pregnancy: Due to the reduced cellular immunity and increased vascularity in genital tractus in pregnancy, AGWs tend to grow more rapidly, to be more in number and friable. Besides, HPV can be transmitted vertically from the mother to the child during delivery which may result in neonatal and congenital, oral, or conjunctival lesions.…”
Section: Special Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicians should suspect for sexual abuse when they encountered with anogenital warts in children. 10,17 Anogenital warts in pregnancy: Due to the reduced cellular immunity and increased vascularity in genital tractus in pregnancy, AGWs tend to grow more rapidly, to be more in number and friable. Besides, HPV can be transmitted vertically from the mother to the child during delivery which may result in neonatal and congenital, oral, or conjunctival lesions.…”
Section: Special Conditionsmentioning
confidence: 99%
“…Cervical cancer: High-risk HPV subtypes (HPV 16 and HPV 18) are the causes of approximately 70% of invasive cervical cancer and it is estimated that 500,000 cases of cervical cancer occur each year worldwide. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] A study of paraffin-embedded samples of 10,575 cases of cervical cancer demonstrated that the most common HPV types were 16,18,31,33,35,45,52, and 58; HPV types 16 and 18 represented 71% of the cases overall. 25 Other anogenital cancers: Vaginal, vulvar, penile and anal cancers and their precancerous precursors such as vulvar intraepithelial neoplasia (IN), penile IN, anal IN are other associated neoplasies.…”
Section: Neoplasiamentioning
confidence: 99%
“…Anogenital verrucae (AV), or condyloma acuminata, are a nonmalignant skin neoplasm caused by the human papillomavirus (HPV). While uncommon in children, exposure can occur in a number of settings: (a) perinatally by passage through the birth canal of an infected mother; (b) nonsexual contact from caregivers; (c) autoinoculation from verrucae on other sites; or (d) sexual abuse . As such, AV in children tend to be caused by a wider array of HPV strains than in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Though spontaneous resolution may occur, parents often seek treatment to mitigate pain, disfigurement, and/or significant physical or psychosocial burden . In addition, AV caused by high‐risk HPV subtypes are at risk for malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Penile warts are the most common sexually transmitted disease in males and are caused by human papillomavirus (HPV) 1–3. Penile warts typically present as soft flesh-colored to brown papules or plaques on the penile shaft and glans penis 4…”
Section: Introductionmentioning
confidence: 99%